Strategy to Improve the Quality of Education at Muara Wis State Junior High School through Strengthening School Management: A Qualitative Analysis of School Management Functions and Implications for Educational Performance - Indang Rusmini; Widyatmike Gede Mulawarman; Khusnul Khotimah (Journal of Pedagogy and Education Science, 2026)
Enhancing educational quality remains a pressing and strategic concern, particularly for schools in remote regions such as Muara Wis State Junior High School. This research investigates strategic efforts to improve educational quality through the reinforcement of school management practices. Employing a qualitative descriptive methodology, data were gathered from selected school principals, teachers, and parents through purposive sampling. The research instruments included in-depth interviews, direct classroom observations, and a review of relevant school documents. The collected data were analyzed using data reduction, thematic categorization, and narrative elaboration. The study indicates that the comprehensive application of fundamental management functions plays a vital role in elevating educational standards. Moreover, effective leadership, infrastructure planning, and financial management emerged as key elements that significantly shape school performance. The interaction between internal factors (e.g., principal leadership) and external influences (e.g., national education policy) was found to contribute jointly to the overall educational quality. The research concludes that school management strengthening should be viewed not only as an administrative necessity but as a strategic approach to achieving long-term improvements in educational outcomes. The insights gained offer valuable direction for policymakers, educators, and stakeholders who seek to adopt effective models of school governance in similar contexts. It is recommended that future studies incorporate mixed-method designs to gain a more comprehensive understanding of how management strategies impact student learning and school effectiveness.